Epoxy fireproof coating and preparation method thereof

By using a combination formula of epoxy fire-retardant coatings in steel structure fire-retardant coatings, and using materials such as silane-modified phenolic epoxy resin and modified alumina, the problem that existing coatings cannot have both anti-corrosion and olefin fire prevention, achieving comprehensive performance of high strength, anti-corrosion, flame retardant and fire-retardant.

CN119529640AActive Publication Date: 2025-02-28GUANGDONG WEIQI NEW MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411921875.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-02-28
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

The existing steel structure expansion fire-retardant coatings cannot have both anti-corrosion properties and fire-retardant functions of olefin fires, which limits its application location.

Method used

An epoxy fire-retardant coating is used, which includes component A and component B. Component A is composed of silane-modified phenolic epoxy resin, aluminum hydroxide, ammonium polyphosphate, alumina fibers, etc. Component B is composed of phenolic amine and 1,3-cyclohexadimethylamine. Through the synergistic action of modified alumina and specific additives, the flame retardant, fire-resistant, high-strength and anti-corrosion properties of the coating are improved.

Benefits of technology

This epoxy fire-retardant coating has good flame retardant, fireproof, high strength and corrosion resistance, and can cure at room temperature. It is suitable for marine oil and gas platforms, petrochemical plant installations and other places, and has broad application prospects.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides an epoxy fireproof coating and a preparation method thereof, and belongs to the technical field of coatings. Comprising a component A and a component B. The component A comprises, by weight, 20-30 parts of silane modified novolac epoxy resin, 5-9 parts of an epoxy reactive diluent, 5-10 parts of aluminum hydroxide, 5-8 parts of melamine, 25-48 parts of ammonium polyphosphate, 0.5-1 part of expanded graphite, 6-8 parts of alumina fiber, 3-10 parts of barium sulfate, 3-5 parts of modified alumina and 2-5 parts of titanium dioxide. The component B is prepared from 40 to 50 parts of phenolic aldehyde amine and 50 to 60 parts of 1, 3-cyclohexanedimethylamine. The coating provided by the invention at least integrates fire prevention performance, corrosion resistance in a marine environment and normal-temperature curing performance, and is applied to fire steel structure fireproof and corrosion-resistant coatings of marine oil and gas platforms, petrochemical plant devices and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coatings, and in particular to an epoxy fire retardant coating and a preparation method thereof. Background Art

[0002] Steel structure fire retardant coatings include two types: expandable and non-expandable. When the expandable fire retardant coating is exposed to fire and heat, the carbonizer is esterified and dehydrated into carbon under the action of the catalyst. The carbide forms a closed three-dimensional honeycomb carbonized layer under the action of the inert gas decomposed by the foaming agent. The carbonized layer can seal the protected substrate and prevent gas diffusion, while preventing external oxygen from diffusing to the surface of the substrate, thereby achieving the purpose of fire prevention and heat insulation.

[0003] The current steel structure intumescent fire retardant coating is composed of organic and inorganic base materials, fire retardant additives, catalysts, foaming agents, etc., and has good fireproof and flame retardant properties. However, the currently prepared fire retardant coating cannot have both anti-corrosion properties and fireproof functions against olefin fires, thus restricting the application of fire retardant coatings. Summary of the invention

[0004] The purpose of the present invention is to propose an epoxy fire retardant coating and a preparation method thereof. The preparation method is simple, and the coating has good flame retardant, fireproof, high-strength and anti-corrosion properties. The coating combines the fireproof properties of olefin fires, the anti-corrosion properties in marine environments and the curing properties at room temperature. The coating is applied to fireproof and anti-corrosion coatings for olefin fire steel structures such as marine oil and gas platforms and petrochemical plant devices, and has broad application prospects.

[0005] The technical solution of the present invention is achieved in this way: The invention provides an epoxy fire retardant coating, comprising a component A and a component B, wherein the component A comprises, by weight, 20-30 parts of silane-modified phenolic epoxy resin, 5-9 parts of epoxy reactive diluent, 5-10 parts of aluminum hydroxide, 5-8 parts of melamine, 25-48 parts of ammonium polyphosphate, 0.5-1 part of expanded graphite, 6-8 parts of aluminum oxide fiber, 3-10 parts of barium sulfate, 3-5 parts of modified aluminum oxide and 2-5 parts of titanium dioxide; In parts by weight, the B component includes 40-50 parts of phenalkamine and 50-60 parts of 1,3-cyclohexanedimethylamine.

[0006] As a further improvement of the present invention, the preparation of the silane-modified phenolic epoxy resin comprises: In parts by weight, 2-5 parts of methylphenyl intermediate silanol, 90-95 parts of phenolic epoxy resin and 3-5 parts of silane coupling agent are added into a reaction container; Stir and heat to 120-130°C, stir and react until the epoxy value of the system is 0.4-0.54 (100g / g) and the viscosity is 3500-6500 (25°C mPa.s), stop stirring and discharge.

[0007] As a further improvement of the present invention, the viscosity of the methylphenyl intermediate silanol is 20-200 (25°C mPa.s), the viscosity of the phenolic epoxy resin is 3500-6000 (25°C mPa.s); the silane coupling agent is γ-glycidyloxypropyltrimethoxysilane. KH560 has excellent surface activity and cross-linking properties.

[0008] Preferably, the novolac epoxy resin can be selected from at least one of o-cresol novolac epoxy resin and bisphenol A novolac epoxy resin.

[0009] As a further improvement of the present invention, the epoxy reactive diluent is C12-14 alkyl glycidyl ether; the particle size of the expanded graphite is 200-400 mesh; the particle size of the expanded graphite is selected to help adjust the viscosity of the coating to ensure better workability, and also to further assist in improving the flame retardant and heat insulating properties of the coating.

[0010] As a further improvement of the present invention, the phenolic epoxy resin is a phenol formaldehyde epoxy resin, which is beneficial to increase the cross-linking density to further improve the heat resistance of the coating.

[0011] Preferably, the epoxy reactive diluent is C12-14 alkyl glycidyl ether, which has good wettability, which is beneficial to improve the dispersibility of the inorganic filler inside the coating on the one hand, and can improve the adhesion of the coating on the other hand.

[0012] Preferably, the epoxy reactive diluent may include ethylene glycol bisglycidyl ether with a diepoxy group.

[0013] As a further improvement of the present invention, the ratio of component A to component B is 7-10:1 by weight.

[0014] As a further improvement of the present invention, in the alumina fiber, the mass ratio of aluminum oxide to silicon dioxide is 60-95:40-5. The composition ratio of the alumina fiber is conducive to further assisting in improving the flame retardancy and heat insulation of the coating.

[0015] As a further improvement of the present invention, the preparation method of the modified alumina is as follows: S1. reacting p-hydroxybenzaldehyde and hexachlorotriphosphazene to obtain HCCP-CHO; S2. The aminosilane coupling agent and HCCP-CHO are reacted to obtain HCCP-silane coupling agent; S3. reacting 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-sulfide with HCCP-silane coupling agent to obtain HCCP-silane coupling agent-DOPS; S4. The alumina and the epoxy silane coupling agent are reacted to obtain a silane coupling agent-modified alumina; S5. reacting HCCP-silane coupling agent-DOPS with silane coupling agent modified alumina to obtain modified alumina.

[0016] As a further improvement of the present invention, the molar ratio of p-hydroxybenzaldehyde to hexachlorotripolyphosphazene in step S1 is 1:6.5-7, the reaction temperature is 65-75°C, and the reaction time is 20-24h; the molar ratio of the aminosilane coupling agent to HCCP-CHO in step S2 is 6.2-6.5:1, the reaction temperature is 95-105°C, and the reaction time is 20-24h, and the aminosilane coupling agent is selected from at least one of KH550, KH602 and KH792; the molar ratio of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-sulfide to HCCP-silane coupling agent in step S3 is 6.2-6.5:1, the reaction temperature is 95-105°C, and the reaction time is 20-24h.

[0017] As a further improvement of the present invention, the mass ratio of alumina to epoxy silane coupling agent in step S4 is 10:3-5, the epoxy silane coupling agent is KH560, the reaction temperature is 40-50°C, and the reaction time is 3-5h; the mass ratio of HCCP-silane coupling agent-DOPS to silane coupling agent modified alumina in step S5 is 2-4:10, the reaction temperature is 45-55°C, and the reaction time is 2-4h.

[0018] The present invention prepares a modified alumina. First, p-hydroxybenzaldehyde and hexachlorotriphosphazene react to obtain HCCP-CHO. The reaction equation is as follows: ; Next, the aminosilane coupling agent reacts with HCCP-CHO, and the aldehyde group on the HCCP-CHO can react with the amino group to produce a C=N bond, and then the C=N can react with 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-sulfide (DPOS), thereby achieving coupling.

[0019] After the surface of alumina powder is modified by a silane coupling agent with an epoxy group, the epoxy group can react with HCCP-silane coupling agent-DOPS and the amino group of the silane coupling agent to achieve coupling. The obtained modified alumina is added to the coating, which greatly improves the fireproof, flame retardant and high-strength properties of the coating. The introduction of sulfur element can enhance the flame retardant effect of phosphorus. Sulfur-containing compounds will decompose at high temperature and release H2 Strong acids such as SO4 promote the dehydration and carbonization of the substrate, so it can also have a good flame retardant effect in the condensed phase. The introduction of silicon elements can form a physical insulating carbon layer with excellent silicon or silicon-carbon bonds, which effectively plays a flame retardant role. In addition, the synergistic flame retardant effect of N, P, Si, and S elements improves the fire safety and smoke suppression performance of the coating.

[0020] The present invention further protects a method for preparing the above-mentioned epoxy fire retardant coating, comprising the following steps: (1) Aluminum hydroxide, melamine, ammonium polyphosphate, expanded graphite, alumina fiber, barium sulfate, modified alumina and titanium dioxide are mixed and ball-milled for 1-3 hours to obtain a mixture; (2) Add the mixture to the silane-modified phenolic epoxy resin, disperse it at 1000-2000 r / min for 10-20 min, add the epoxy reactive diluent, continue to disperse it for 5-10 min, then add the phenolic amine and 1,3-cyclohexanedimethylamine, stir and mix for 15-20 min to obtain the epoxy fire retardant coating.

[0021] The present invention has the following beneficial effects: In the present invention, since the side chain of the silane-modified phenolic epoxy resin contains aromatic rings, the coating has good radiation resistance, which is beneficial to reduce the degradation caused by radiation. In addition, the silane-modified phenolic epoxy resin is compounded with amines such as melamine, phenolic amine, 1,3-cyclohexanedimethylamine, so that the coating can be cured at room temperature, and can also improve the fire-resistant time, fire-resistant stability and have excellent expansion and heat insulation effect. In addition, the dehydration carbonization catalyst ammonium polyphosphate and the flame retardant aluminum hydroxide are deaminated to generate phosphoric acid at a high temperature above 160°C, and then generate polyphosphoric acid, and then react with hydroxyl-containing molecular chains, such as phenolic resin and epoxy resin. In the reaction process, polyphosphoric acid is repeatedly generated, which is a very strong dehydrating agent, and a large amount of water is taken off in the reaction, thereby changing the chemical process of the organic thermal decomposition reaction, making the hydroxyl-containing organic dehydration reaction generate an unsaturated main chain, and then by the cyclization bridging reaction, a good carbonized layer is formed. In addition, the present invention uses melamine and expanded graphite as a foaming agent, and the foaming agent and the dehydration carbonization catalyst selected in the present invention can synergistically form a good foam carbonization layer, thereby solving the problem of the carbonization layer being lifted up or the flame retardant gas overflowing, thereby further improving the fire resistance. In addition, the compounding of alumina fiber, barium sulfate and titanium dioxide with resin is also conducive to further improving the anti-corrosion performance and fire retardant effect of the coating. DETAILED DESCRIPTION

[0022] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] The model of phenolic epoxy resin is F-51, the viscosity is 3500-6000 (25℃ mPa.s), the corresponding manufacturer model is WE-8401, and the manufacturer is Guangzhou WeiChuang High-tech Materials Technology Co., Ltd.

[0024] The CAS number of the methylphenyl intermediate silanol is 5272-18-4, the viscosity is 20-200 (25°C mPa.s), and the manufacturer is Beijing Bailingwei Technology Co., Ltd.

[0025] Preparation Example 1 Preparation of silane-modified phenolic epoxy resin include: In parts by weight, add 2 parts of methylphenyl intermediate silanol, 90 parts of phenolic epoxy resin and 3 parts of γ-glycidyloxypropyltrimethoxysilane into the reaction container; stir and heat to 120°C, stir and react until the epoxy value of the system is 0.4 (100g / g) and the viscosity is 3500 (25°C mPa.s), stop stirring and discharge.

[0026] Preparation Example 2 Preparation of Silane-modified Novolac Epoxy Resin include: In parts by weight, add 5 parts of methylphenyl intermediate silanol, 95 parts of phenolic epoxy resin and 5 parts of γ-glycidyloxypropyltrimethoxysilane into the reaction container; stir and heat to 130°C, stir and react until the epoxy value of the system is 0.54 (100g / g) and the viscosity is 6500 (25°C mPa.s), stop stirring and discharge.

[0027] Preparation Example 3 Preparation of Silane-modified Novolac Epoxy Resin include: In parts by weight, 3.5 parts of methylphenyl intermediate silanol, 92 parts of phenolic epoxy resin and 4 parts of γ-glycidyloxypropyltrimethoxysilane were added to the reaction container; stirred and heated to 125°C, stirred and reacted until the epoxy value of the system was 0.47 (100g / g) and the viscosity was 5000 (25°C mPa.s), then the stirring was stopped and the material was discharged.

[0028] Preparation Example 4 Preparation of modified alumina Here’s how: S1. 0.65 mol of p-hydroxybenzaldehyde, 0.7 mol of anhydrous sodium carbonate and 500 mL of tetrahydrofuran were stirred and mixed to dissolve, and 100 mL of 0.1 mol of tetrahydrofuran solution of hexachlorotriphosphazene was added dropwise. After the addition was completed, the mixture was heated to 65°C and stirred for reaction for 20 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed and dried to obtain HCCP-CHO with a yield of 90%; S2. 0.62 mol of silane coupling agent KH550, 0.1 mol of HCCP-CHO and 500 mL of 1,4-dioxane were mixed evenly, heated to 95°C, stirred and reacted for 20 hours. After the reaction was completed, it was cooled to room temperature, filtered, washed and dried to obtain HCCP-silane coupling agent with a yield of 82%; S3. 0.62 mol 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-sulfide, 0.1 mol HCCP-silane coupling agent and 500 mL 1,4-dioxane were mixed evenly, heated to 95°C under nitrogen protection, stirred and reacted for 20 hours. After the reaction was completed, it was cooled to room temperature, filtered, washed and dried to obtain HCCP-silane coupling agent-DOPS; S4. 10 g of aluminum oxide and 3 g of silane coupling agent KH560 were added to 200 mL of ethanol, heated to 40° C., stirred for reaction for 3 h, filtered, washed, and dried to obtain silane coupling agent-modified aluminum oxide; S5. Add 2 g HCCP-silane coupling agent-DOPS and 10 g silane coupling agent modified alumina into 200 mL ethanol, heat to 45° C., stir to react for 2 h, filter, wash, and dry to obtain modified alumina.

[0029] Preparation Example 5 Preparation of modified alumina Here’s how: S1. 0.7 mol of p-hydroxybenzaldehyde, 0.7 mol of anhydrous sodium carbonate and 500 mL of tetrahydrofuran were stirred and mixed to dissolve, and 100 mL of 0.1 mol of tetrahydrofuran solution of hexachlorotriphosphazene was added dropwise. After the addition was completed, the mixture was heated to 75°C and stirred for reaction for 24 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed and dried to obtain HCCP-CHO with a yield of 92%; S2. 0.65 mol of silane coupling agent KH792, 0.1 mol of HCCP-CHO and 500 mL of 1,4-dioxane were mixed evenly, heated to 105°C, stirred and reacted for 24 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed and dried to obtain HCCP-silane coupling agent with a yield of 85%; S3. 0.65 mol 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-sulfide, 0.1 mol HCCP-silane coupling agent and 500 mL 1,4-dioxane were mixed evenly, heated to 105°C under nitrogen protection, stirred and reacted for 24 hours. After the reaction was completed, it was cooled to room temperature, filtered, washed and dried to obtain HCCP-silane coupling agent-DOPS; S4. 10 g of alumina and 5 g of silane coupling agent KH560 were added to 200 mL of ethanol, heated to 50° C., stirred for reaction for 5 h, filtered, washed, and dried to obtain silane coupling agent-modified alumina; S5. Add 4 g HCCP-silane coupling agent-DOPS and 10 g silane coupling agent modified alumina into 200 mL ethanol, heat to 55° C., stir and react for 4 h, filter, wash and dry to obtain modified alumina.

[0030] Preparation Example 6 Preparation of modified alumina Here’s how: S1. 0.67 mol of p-hydroxybenzaldehyde, 0.7 mol of anhydrous sodium carbonate and 500 mL of tetrahydrofuran were stirred and mixed to dissolve, and 100 mL of 0.1 mol of tetrahydrofuran solution of hexachlorotriphosphazene was added dropwise. After the addition was completed, the mixture was heated to 70°C and stirred for reaction for 22 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed and dried to obtain HCCP-CHO with a yield of 90%; S2. 0.63 mol of silane coupling agent KH602, 0.1 mol of HCCP-CHO and 500 mL of 1,4-dioxane were mixed evenly, heated to 100°C, stirred and reacted for 22 hours. After the reaction was completed, it was cooled to room temperature, filtered, washed and dried to obtain HCCP-silane coupling agent with a yield of 82%; S3. 0.63 mol 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-sulfide, 0.1 mol HCCP-silane coupling agent and 500 mL 1,4-dioxane were mixed evenly, heated to 100°C under nitrogen protection, stirred and reacted for 22 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed and dried to obtain HCCP-silane coupling agent-DOPS; S4. 10 g of alumina and 4 g of silane coupling agent KH560 were added to 200 mL of ethanol, heated to 45° C., stirred for reaction for 4 h, filtered, washed, and dried to obtain silane coupling agent-modified alumina; S5. Add 3 g HCCP-silane coupling agent-DOPS and 10 g silane coupling agent modified alumina into 200 mL ethanol, heat to 50° C., stir and react for 3 h, filter, wash and dry to obtain modified alumina.

[0031] Comparative Preparation Example 1 Compared with Preparation Example 6, the difference is that step S3 is not performed.

[0032] The details are as follows: S1. 0.67 mol of p-hydroxybenzaldehyde, 0.7 mol of anhydrous sodium carbonate and 500 mL of tetrahydrofuran were stirred and mixed to dissolve, and 100 mL of 0.1 mol of tetrahydrofuran solution of hexachlorotriphosphazene was added dropwise. After the addition was completed, the mixture was heated to 70°C and stirred for reaction for 22 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed and dried to obtain HCCP-CHO with a yield of 90%; S2. 0.63 mol of silane coupling agent KH602, 0.1 mol of HCCP-CHO and 500 mL of 1,4-dioxane were mixed evenly, heated to 100°C, stirred and reacted for 22 hours. After the reaction was completed, it was cooled to room temperature, filtered, washed and dried to obtain HCCP-silane coupling agent with a yield of 82%; S3. 10 g of alumina and 4 g of silane coupling agent KH560 were added to 200 mL of ethanol, heated to 45° C., stirred for reaction for 4 h, filtered, washed, and dried to obtain silane coupling agent-modified alumina; S4. Add 3 g of HCCP-silane coupling agent and 10 g of silane coupling agent-modified alumina into 200 mL of ethanol, heat to 50° C., stir and react for 3 h, filter, wash and dry to obtain modified alumina.

[0033] Comparative Preparation Example 2 Compared with Preparation Example 6, the difference is that steps S2 and S3 are not performed, and the silane coupling agent KH560 in step S4 is replaced by KH550.

[0034] The details are as follows: S1. 0.67 mol of p-hydroxybenzaldehyde, 0.7 mol of anhydrous sodium carbonate and 500 mL of tetrahydrofuran were stirred and mixed to dissolve, and 100 mL of 0.1 mol of tetrahydrofuran solution of hexachlorotriphosphazene was added dropwise. After the addition was completed, the mixture was heated to 70°C and stirred for reaction for 22 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed and dried to obtain HCCP-CHO with a yield of 90%; S2. 10 g of alumina and 4 g of silane coupling agent KH550 were added to 200 mL of ethanol, heated to 45° C., stirred for reaction for 4 h, filtered, washed, and dried to obtain silane coupling agent-modified alumina; S3. Add 3 g HCCP-CHO and 10 g silane coupling agent modified alumina into 200 mL ethanol, heat to 50° C., stir and react for 3 h, filter, wash and dry to obtain modified alumina.

[0035] Example 1 An epoxy fire retardant coating, comprising component A and component B, characterized in that, by weight, the component A comprises 20 parts of silane-modified phenolic epoxy resin prepared in Preparation Example 1, 5 parts of ethylene glycol diglycidyl ether with diepoxy groups, 5 parts of aluminum hydroxide, 5 parts of melamine, 25 parts of ammonium polyphosphate, 0.5 parts of expanded graphite, 6 parts of alumina fiber, 3 parts of barium sulfate, 3 parts of modified alumina prepared in Preparation Example 4, and 2 parts of titanium dioxide. In the alumina fiber, the mass ratio of aluminum oxide to silicon dioxide is 60:40.

[0036] The particle size of the expanded graphite is 300 meshes; and the phenolic epoxy resin is phenol formaldehyde epoxy resin.

[0037] In parts by weight, the B component includes 40 parts of phenalkamine and 50 parts of 1,3-cyclohexanedimethylamine.

[0038] In parts by weight, the ratio of component A to component B is 10:1.

[0039] The preparation method comprises the following steps: (1) Aluminum hydroxide, melamine, ammonium polyphosphate, expanded graphite, alumina fiber, barium sulfate, modified alumina and titanium dioxide are mixed and ball-milled for 1 hour to obtain a mixture; (2) Add the mixture to the silane-modified phenolic epoxy resin, disperse it at 1000 r / min for 10 min, add the epoxy reactive diluent, continue to disperse it for 5 min, then add the phenolic amine and 1,3-cyclohexanedimethylamine, stir and mix for 15 min to obtain the epoxy fire retardant coating.

[0040] Example 2 An epoxy fire retardant coating, comprising component A and component B, characterized in that, by weight, the component A comprises 30 parts of silane-modified phenolic epoxy resin prepared in Preparation Example 2, 9 parts of ethylene glycol diglycidyl ether with diepoxy groups, 10 parts of aluminum hydroxide, 8 parts of melamine, 48 parts of ammonium polyphosphate, 1 part of expanded graphite, 8 parts of alumina fiber, 10 parts of barium sulfate, 5 parts of modified alumina prepared in Preparation Example 5, and 5 parts of titanium dioxide. In the alumina fiber, the mass ratio of aluminum oxide to silicon dioxide is 95:5.

[0041] The particle size of the expanded graphite is 400 meshes; and the phenolic epoxy resin is phenol formaldehyde epoxy resin.

[0042] In parts by weight, the B component includes 50 parts of phenalkamine and 60 parts of 1,3-cyclohexanedimethylamine.

[0043] In parts by weight, the ratio of component A to component B is 10:1.

[0044] The preparation method comprises the following steps: (1) Aluminum hydroxide, melamine, ammonium polyphosphate, expanded graphite, alumina fiber, barium sulfate, modified alumina and titanium dioxide are mixed and ball-milled for 3 hours to obtain a mixture; (2) Add the mixture to silane-modified phenolic epoxy resin and disperse it at 2000 r / min for 20 min. Add diepoxy ethylene glycol diglycidyl ether and continue to disperse it for 10 min. Then add phenolic amine and 1,3-cyclohexanedimethylamine and stir and mix for 20 min to obtain an epoxy fire retardant coating.

[0045] Example 3 An epoxy fire retardant coating, comprising component A and component B, characterized in that, by weight, the component A comprises 25 parts of silane-modified phenolic epoxy resin prepared in Preparation Example 3, 7 parts of ethylene glycol diglycidyl ether with diepoxy groups, 7 parts of aluminum hydroxide, 7 parts of melamine, 39 parts of ammonium polyphosphate, 0.7 parts of expanded graphite, 7 parts of alumina fiber, 7 parts of barium sulfate, 4 parts of modified alumina prepared in Preparation Example 6, and 3 parts of titanium dioxide. In the alumina fiber, the mass ratio of aluminum oxide to silicon dioxide is 75:25.

[0046] The particle size of the expanded graphite is 200 meshes; the phenolic epoxy resin is phenol formaldehyde epoxy resin.

[0047] In parts by weight, the B component includes 45 parts of phenalkamine and 55 parts of 1,3-cyclohexanedimethylamine.

[0048] In parts by weight, the ratio of component A to component B is 9:1.

[0049] The preparation method comprises the following steps: (1) Aluminum hydroxide, melamine, ammonium polyphosphate, expanded graphite, alumina fiber, barium sulfate, modified alumina and titanium dioxide are mixed and ball-milled for 2 hours to obtain a mixture; (2) The mixture was added to the silane-modified phenolic epoxy resin and dispersed at 1500 r / min for 15 min. Diepoxy-containing ethylene glycol diglycidyl ether was added and the dispersion was continued for 7 min. Then, phenolic amine and 1,3-cyclohexanedimethylamine were added and the mixture was stirred and mixed for 17 min to obtain an epoxy fire retardant coating.

[0050] Comparative Example 1 Compared with Example 3, the difference is that the modified alumina is prepared by Comparative Preparation Example 1.

[0051] Comparative Example 2 Compared with Example 3, the difference is that the modified alumina is prepared by Comparative Preparation Example 2.

[0052] Comparative Example 3 The difference compared with Example 3 is that no modified alumina is added.

[0053] The details are as follows: An epoxy fire retardant coating, comprising component A and component B, characterized in that, by weight, the component A comprises 25 parts of silane-modified phenolic epoxy resin prepared in Preparation Example 3, 7 parts of ethylene glycol diglycidyl ether with diepoxy groups, 7 parts of aluminum hydroxide, 7 parts of melamine, 39 parts of ammonium polyphosphate, 0.7 parts of expanded graphite, 7 parts of alumina fiber, 7 parts of barium sulfate, 4 parts of modified alumina prepared in Preparation Example 6, and 3 parts of titanium dioxide. In the alumina fiber, the mass ratio of aluminum oxide to silicon dioxide is 75:25.

[0054] The particle size of the expanded graphite is 200 meshes; the phenolic epoxy resin is phenol formaldehyde epoxy resin.

[0055] In parts by weight, the B component includes 45 parts of phenalkamine and 55 parts of 1,3-cyclohexanedimethylamine.

[0056] In parts by weight, the ratio of component A to component B is 9:1.

[0057] The preparation method comprises the following steps: (1) Aluminum hydroxide, melamine, ammonium polyphosphate, expanded graphite, alumina fiber, barium sulfate, modified alumina and titanium dioxide are mixed and ball-milled for 2 hours to obtain a mixture; (2) The mixture was added to the silane-modified phenolic epoxy resin and dispersed at 1500 r / min for 15 min. Diepoxy-containing ethylene glycol diglycidyl ether was added and the dispersion was continued for 7 min. Then, phenolic amine and 1,3-cyclohexanedimethylamine were added and the mixture was stirred and mixed for 17 min to obtain an epoxy fire retardant coating.

[0058] Comparative Example 4 Compared with Example 3, the difference is that the silane-modified phenolic epoxy resin is replaced by an equal mass of phenolic epoxy resin.

[0059] Comparative Example 5 Compared with Example 3, the difference is that no melamine is added.

[0060] The details are as follows: An epoxy fire retardant coating, comprising component A and component B, characterized in that, by weight, the component A comprises 25 parts of silane-modified phenolic epoxy resin prepared in Preparation Example 3, 7 parts of ethylene glycol diglycidyl ether with diepoxy groups, 7 parts of aluminum hydroxide, 39 parts of ammonium polyphosphate, 7.7 parts of expanded graphite, 7 parts of alumina fiber, 7 parts of barium sulfate, 4 parts of modified alumina prepared in Preparation Example 6, and 3 parts of titanium dioxide. In the alumina fiber, the mass ratio of aluminum oxide to silicon dioxide is 75:25.

[0061] The particle size of the expanded graphite is 200 meshes; the phenolic epoxy resin is phenol formaldehyde epoxy resin.

[0062] In parts by weight, the B component includes 45 parts of phenalkamine and 55 parts of 1,3-cyclohexanedimethylamine.

[0063] In parts by weight, the ratio of component A to component B is 9:1.

[0064] The preparation method comprises the following steps: (1) Aluminum hydroxide, ammonium polyphosphate, expanded graphite, alumina fiber, barium sulfate, modified alumina and titanium dioxide are mixed and ball-milled for 2 hours to obtain a mixture; (2) The mixture was added to the silane-modified phenolic epoxy resin and dispersed at 1500 r / min for 15 min. Diepoxy-containing ethylene glycol diglycidyl ether was added and the dispersion was continued for 7 min. Then, phenolic amine and 1,3-cyclohexanedimethylamine were added and the mixture was stirred and mixed for 17 min to obtain an epoxy fire retardant coating.

[0065] Comparative Example 6 The difference compared with Example 3 is that no expanded graphite is added.

[0066] The details are as follows: An epoxy fire retardant coating, comprising component A and component B, characterized in that, by weight, the component A comprises 25 parts of silane-modified phenolic epoxy resin prepared in Preparation Example 3, 7 parts of ethylene glycol diglycidyl ether with diepoxy groups, 7 parts of aluminum hydroxide, 7.7 parts of melamine, 39 parts of ammonium polyphosphate, 7 parts of alumina fiber, 7 parts of barium sulfate, 4 parts of modified alumina prepared in Preparation Example 6, and 3 parts of titanium dioxide. In the alumina fiber, the mass ratio of aluminum oxide to silicon dioxide is 75:25.

[0067] The particle size of the expanded graphite is 200 meshes; the phenolic epoxy resin is phenol formaldehyde epoxy resin.

[0068] In parts by weight, the B component includes 45 parts of phenalkamine and 55 parts of 1,3-cyclohexanedimethylamine.

[0069] In parts by weight, the ratio of component A to component B is 9:1.

[0070] The preparation method comprises the following steps: (1) Aluminum hydroxide, melamine, ammonium polyphosphate, alumina fiber, barium sulfate, modified alumina and titanium dioxide are mixed and ball-milled for 2 hours to obtain a mixture; (2) The mixture was added to the silane-modified phenolic epoxy resin and dispersed at 1500 r / min for 15 min. Diepoxy-containing ethylene glycol diglycidyl ether was added and the dispersion was continued for 7 min. Then, phenolic amine and 1,3-cyclohexanedimethylamine were added and the mixture was stirred and mixed for 17 min to obtain an epoxy fire retardant coating.

[0071] Comparative Example 7 Compared with Example 3, the difference is that melamine and expanded graphite are not added.

[0072] The details are as follows: An epoxy fire retardant coating, comprising component A and component B, characterized in that, by weight, the component A comprises 25 parts of silane-modified phenolic epoxy resin prepared in Preparation Example 3, 7 parts of ethylene glycol diglycidyl ether with diepoxy groups, 7 parts of aluminum hydroxide, 39 parts of ammonium polyphosphate, 7 parts of alumina fiber, 7 parts of barium sulfate, 4 parts of modified alumina prepared in Preparation Example 6, and 3 parts of titanium dioxide. In the alumina fiber, the mass ratio of aluminum oxide to silicon dioxide is 75:25.

[0073] The particle size of the expanded graphite is 200 meshes; the phenolic epoxy resin is phenol formaldehyde epoxy resin.

[0074] In parts by weight, the B component includes 45 parts of phenalkamine and 55 parts of 1,3-cyclohexanedimethylamine.

[0075] In parts by weight, the ratio of component A to component B is 9:1.

[0076] The preparation method comprises the following steps: (1) Aluminum hydroxide, ammonium polyphosphate, alumina fiber, barium sulfate, modified alumina and titanium dioxide are mixed and ball-milled for 2 hours to obtain a mixture; (2) The mixture was added to the silane-modified phenolic epoxy resin and dispersed at 1500 r / min for 15 min. Diepoxy-containing ethylene glycol diglycidyl ether was added and the dispersion was continued for 7 min. Then, phenolic amine and 1,3-cyclohexanedimethylamine were added and the mixture was stirred and mixed for 17 min to obtain an epoxy fire retardant coating.

[0077] Test Example 1 The performance of the epoxy fire retardant coatings prepared in Examples 1-3 and Comparative Examples 1-7 was tested, and the results are shown in Table 1.

[0078] (1) State in the container: After stirring, the paint is observed to be uniform and fine or thick and fluid, without any lumps, and is qualified.

[0079] (2) Surface drying time, initial drying crack resistance, bonding strength and fire resistance can all be measured according to the corresponding parts of the national standard GB14907-2018.

[0080] (3) Salt spray resistance: Tested according to the requirements of GB / T1766-2008, the longest time without cracking, peeling, rusting and blistering.

[0081] (4) Artificial aging: Test according to the requirements of GB / T1766-2008 to determine the longest time without cracking, peeling, rusting or blistering.

[0082] (5) Water resistance test: Use procedure B of NB / T20133.5-2012 to test the longest time without cracking, peeling, rusting and blistering. Slight uniform changes in color and gloss are allowed and it is judged as compliance.

[0083] Table 1 Group Initial drying crack resistance Status in the container Surface drying time (h) Bond strength / MPa Fire resistance limit (h) Salt spray resistance time (h) Artificial aging resistance time (h) Water resistance time (d) Example 1 No cracks qualified 4 2.7 4.5 9270 1500 265 Example 2 No cracks qualified 4 2.6 4.4 9300 1550 262 Example 3 No cracks qualified 4 2.8 4.7 9380 1520 267 Comparative Example 1 No cracks qualified 4 2.4 3.7 9230 1340 252 Comparative Example 2 No cracks qualified 4 2.3 3.5 9210 1310 250 Comparative Example 3 No cracks qualified 4 2.2 3.0 9200 1250 240 Comparative Example 4 There are cracks qualified 5 2.0 4.1 8850 970 248 Comparative Example 5 No cracks qualified 4.2 2.3 3.5 9050 1550 240 Comparative Example 6 No cracks qualified 4.3 2.2 3.4 9070 1580 251 Comparative Example 7 No cracks qualified 4.6 2.2 2.8 9010 1480 239 It can be seen from the above table that the epoxy fire retardant coatings prepared in Examples 1-3 of the present invention have good comprehensive properties.

[0084] Test Example 2 The performance of the epoxy fire retardant coatings prepared in Examples 1-3 and Comparative Examples 1-7 was tested, and the results are shown in Table 2.

[0085] Limiting oxygen index (LOI): Refer to the national standard GB / T 2406.1-2008, and use JF-5 limiting oxygen index tester for measurement. The sample size is 80 (±5) mm × 6.5 (±0.5) mm × 3.0 (±0.25) mm.

[0086] Vertical combustion (UL-94): Refer to the national standard GB / T 2408-2021, and use CZF-5 vertical combustion tester for testing. The sample size is 125 (±5) mm × 13.0 (±0.3) mm × 3.0 (±0.2) mm.

[0087] Table 2 Group LOI (%) UL-94 Example 1 36.7 V-0 Example 2 36.4 V-0 Example 3 36.9 V-0 Comparative Example 1 33.1 V-0 Comparative Example 2 32.7 V-0 Comparative Example 3 26.1 V-2 Comparative Example 4 34.8 V-0 Comparative Example 5 31.0 V-0 Comparative Example 6 30.4 V-1 Comparative Example 7 28.1 V-1 It can be seen from the above table that the epoxy fire retardant coatings prepared in Examples 1-3 of the present invention have good flame retardant properties.

[0088] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. An epoxy fire retardant coating, comprising component A and component B, characterized in that: In parts by weight, the component A comprises 20-30 parts of silane-modified phenolic epoxy resin, 5-9 parts of epoxy reactive diluent, 5-10 parts of aluminum hydroxide, 5-8 parts of melamine, 25-48 parts of ammonium polyphosphate, 0.5-1 parts of expanded graphite, 6-8 parts of alumina fiber, 3-10 parts of barium sulfate, 3-5 parts of modified alumina and 2-5 parts of titanium dioxide; In parts by weight, the B component includes 40-50 parts of phenalkamine and 50-60 parts of 1,3-cyclohexanedimethylamine.

2. The epoxy fire retardant coating according to claim 1, characterized in that: The preparation of the silane-modified phenolic epoxy resin comprises: In parts by weight, 2-5 parts of methylphenyl intermediate silanol, 90-95 parts of phenolic epoxy resin and 3-5 parts of silane coupling agent are added into a reaction container; Stir and heat to 120-130°C, stir and react until the epoxy value of the system is 0.4-0.54 (100g / g) and the viscosity is 3500-6500 (25°C mPa.s), stop stirring and discharge.

3. The epoxy fire retardant coating according to claim 2, characterized in that: The viscosity of the methylphenyl intermediate silanol is 20-200 (25°C mPa.s), the viscosity of the phenolic epoxy resin is 3500-6000 (25°C mPa.s); and the silane coupling agent is γ-glycidyloxypropyltrimethoxysilane.

4. The epoxy fire retardant coating according to claim 1, characterized in that: The epoxy active diluent is C12-14 alkyl glycidyl ether; the particle size of the expanded graphite is 200-400 meshes; and the phenolic epoxy resin is phenol formaldehyde epoxy resin.

5. The epoxy fire retardant coating according to claim 1, characterized in that: By weight, the ratio of component A to component B is 7-10:

1.

6. The epoxy fire retardant coating according to claim 1, characterized in that: In the alumina fiber, the mass ratio of aluminum oxide to silicon dioxide is 60-95:40-5.

7. The epoxy fire retardant coating according to claim 1, characterized in that: The preparation method of the modified alumina is as follows: S1. The p-hydroxybenzaldehyde and hexachlorotriphosphazene are reacted to obtain HCCP-CHO; S2. The aminosilane coupling agent and HCCP-CHO are reacted to obtain HCCP-silane coupling agent; S3. reacting 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-sulfide with HCCP-silane coupling agent to obtain HCCP-silane coupling agent-DOPS; S4. The alumina and the epoxy silane coupling agent are reacted to obtain a silane coupling agent-modified alumina; S5. reacting HCCP-silane coupling agent-DOPS with silane coupling agent modified alumina to obtain modified alumina.

8. The epoxy fire retardant coating according to claim 7, characterized in that: The molar ratio of p-hydroxybenzaldehyde to hexachlorotripolyphosphazene in step S1 is 1:6.5-7, the reaction temperature is 65-75°C, and the reaction time is 20-24h; the molar ratio of the aminosilane coupling agent to HCCP-CHO in step S2 is 6.2-6.5:1, the reaction temperature is 95-105°C, and the reaction time is 20-24h, and the aminosilane coupling agent is selected from at least one of KH550, KH602 and KH792; the molar ratio of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-sulfide to HCCP-silane coupling agent in step S3 is 6.2-6.5:1, the reaction temperature is 95-105°C, and the reaction time is 20-24h.

9. The epoxy fire retardant coating according to claim 7, characterized in that: In step S4, the mass ratio of alumina to epoxy silane coupling agent is 10:3-5, the epoxy silane coupling agent is KH560, the reaction temperature is 40-50°C, and the reaction time is 3-5h; in step S5, the mass ratio of HCCP-silane coupling agent-DOPS to silane coupling agent modified alumina is 2-4:10, the reaction temperature is 45-55°C, and the reaction time is 2-4h.

10. A method for preparing the epoxy fire retardant coating according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) Aluminum hydroxide, melamine, ammonium polyphosphate, expanded graphite, alumina fiber, barium sulfate, modified alumina and titanium dioxide are mixed and ball-milled for 1-3 hours to obtain a mixture; (2) Add the mixture to the silane-modified phenolic epoxy resin, disperse it at 1000-2000 r / min for 10-20 min, add the epoxy reactive diluent, continue to disperse it for 5-10 min, then add the phenolic amine and 1,3-cyclohexanedimethylamine, stir and mix for 15-20 min to obtain the epoxy fire retardant coating.

Citation Information

Patent Citations

  • Epoxy-based fireproof coating with steel structure

    CN110760244A

  • Intumescent epoxy fireproof coating as well as preparation method and application thereof

    CN116925618A

  • Polyorganosilicone cyclophosphazene modified epoxy resin and preparation method thereof

    CN119286192A

  • Organosilicon cyclophosphazene modified epoxy resin and preparation method thereof

    CN119371780A

  • Epoxy-resin intumescent fire-resistant coating for steel structure use, and method for fabrication thereof

    WO2018095361A1

Cited By

  • Graphite fireproof coating and preparation method thereof

    CN120365800A